Selected Lectures of the Balkan Meeting of Neonatology; Cagliari (Italy); October 25, 2024 - - (Hygeia Press di Corridori Marinella, 2024)
Selected Lectures of the Balkan Meeting of Neonatology; Cagliari (Italy); October 25th, 2024 The Balkan Meeting of Neonatology is a Satellite Meeting of the 20th International Workshop on Neonatology and Pediatrics, Cagliari (Italy), October 23rd-26th, 2024.   LECT 1. MORTALITY RATE OF PRETERM BABIES BORN IN THE TERTIARY MEDICAL CENTER IN TIRANA AND THE IMPACT OF THE IMPROVEMENT OF THE KNOWLEDGE AND SKILLS OF THE HEALTH STAFF • A. Hoxha-Qosja (Tirana, Albania) LECT 2. THE IMPACT OF EARLY CPAP IN THE DELIVERY ROOM IN PRETERM INFANTS WITH A GESTATIONAL AGE OF 31-36+6 WEEKS • M. Meta, A. Hoxha-Qosja (Fier and Tirana, Albania) LECT 3. IMPACT OF NEONATAL EARLY-ONSET SEPSIS CALCULATOR IN OUR CLINICAL PRACTICE • G. Koroveshi-Gora, A. Hoxha-Qosja, S. Damo (Tirana, Albania) LECT 4. MATERNAL DIET AND BREASTFEEDING • S. Deantoni, E. Bertino, C. Peila, S. Gandino, A. Coscia (Turin and Moncalieri, Italy) LECT 5. NUTRITION AND GROWTH OF PRETERM BABIES IN NICUs • E. Hatzidaki (Heraklion, Greece) LECT 6. NEONATAL SKIN AND RARE DISEASES • S. Savasta (Cagliari, Italy) LECT 7. PREVENTION AND EARLY CARE OF PRESSURE ULCERS IN THE NICU SETTING: A QUALITY IMPROVEMENT PROJECT • G. Ciprandi (Rome, Italy) LECT 8. SEPSIS AND ITS TREATMENT FROM NEWBORNS TO ADULTS • G. Finco (Cagliari, Italy) LECT 9. ARTIFICIAL INTELLIGENCE IN NEONATOLOGY • K.K. Kopeć, A. Noto, C. Piras, M. Spada, L. Atzori, V. Fanos (Cagliari, Italy) LECT 10. AUTISTIC SPECTRUM DISORDERS IN NICU CANDIDATES • E. Tsekoura (Athens, Greece) LECT 11. RESPIRATORY SYNCYTIAL VIRUS (RSV) INFECTION: NOT ONLY PRETERM INFANTS • E. Lanfranchi (Urbino, Italy)